SDLC MODEL FOR IMPLEMENTATION OF E-BLANGKO ON DEPARTMENT OF POPULATION AND CIVIL REGISTRATION - Handha Zenita; Rina Fiati (Lambung Mangkurat University, 2019)
Utilization of Information and Communication Technology (ICT) in the Secretariat of the Population and Civil Registration Office of the Regency of Kudus is a necessity to assist in facilitating data management, so that the effectiveness and efficiency of performance can be achieved. One of the data management is Blank Management. The blank management process starts from blank data collection, then conducts the transaction process which includes procurement and use of blanks, as well as printing monthly reports and global reports / annual reports. The purpose of this study is to streamline time and to facilitate the user in helping the blank management process. The software used for the implementation of E-Blangko is Sublime Text with the PHP programming language, while MySQL is used as a Database. The method used in the implementation of E-Blangko is the System Development Life Cycle (SDLC) method. SDLC or System Development Life Cycle is the process of developing or changing a software system using models and methods used to develop previous software systems. The system development life cycle or SDLC is a methodology for designing, building, and maintaining information and system processes. The results of this study are that the E-Blangko application can be used for blank management, conducting procurement and use transactions, printing reports, can make it easier for users to perform receipts from each blank, and are expected to be in accordance with needs and be more effective and efficient.Keywords: E-blangko, Technology, Information, Systems.Pemanfaatan Teknologi Informasi dan Komunikasi (TIK) pada bagian Sekretariat Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kudus menjadi suatu kebutuhan untuk membantu dalam mempermudah pengelolaan data, sehingga efektifitas dan efisiensi kinerja dapat tercapai. Salah satu pengelolaan data yang adalah Pengelolaan Blangko. Proses pengelolaan blangko dimulai dari pendataan jenis blangko, kemudian melakukan proses transaksi yang meliputi pengadaan dan penggunaan blangko, serta mencetak laporan bulanan maupun laporan global/laporan tahunan. Tujuan dari penelitian ini adalah untuk mengefisiensikan waktu dan untuk mempermudah user dalam membantu proses pengelolaan blangko. Software yang digunakan untuk implementasi E-Blangko adalah Sublime Text dengan bahasa pemrograman PHP, sedangkan MySQL digunakan sebagai Database. Metode yang digunakan dalam implementasi E-Blangko adalah metode System Development Life Cycle (SDLC). SDLC atau System Development Life Cycle adalah proses mengembangkan atau mengubah suatu sistem perangkat lunak dengan menggunakan model-model dan metode-metodologi yang digunakan untuk mengembangkan sistem-sistem perangkat lunak sebelumnya. Siklus hidup pengembangan sistem atau SDLC adalah metodologi untuk merancang, membangun, dan memelihara informasi dan proses sistem. Hasil dari penelitian ini adalah aplikasi E-Blangko dapat digunakan untuk pengelolaan blangko, melakukan transaksi pengadaan dan penggunaan, melakukan cetak laporan, dapat mempermudah user untuk melakukan perhitugan dari setiap blangko, dan diharapkan sesuai dengan kebutuhan dan menjadi lebih efektif dan efisien dalam menghasilkan suatu informasi.Kata kunci: E-Blangko, Teknologi, Informasi, Sistem.